2012
DOI: 10.5120/8450-2245
|View full text |Cite
|
Sign up to set email alerts
|

Election Results Prediction System based on Fuzzy Logic

Abstract: Election is very popular word in the universe. As per the definition, Election is a process to select suitable from a group of candidates. But the process and properties may vary for different sectors. It has different types. Like local election, legislative election, parliamentary election, presidential election, senate election or election in a small group / union. As election is very famous same way election prediction is again not a new keyword. It has same long life as election. But still there is a chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Logika fuzzy adalah suatu cara yang tepat untuk memetakan suatu ruang input ke dalam suatu ruang output [2]. Sistem Fuzzy Inference (FIS) menggunakan fuzzy set dan aturan "IF-THEN" yang relevan dengan fuzzy set untuk membuat keputusan tentang informasi yang tidak lengkap atau samar, metode Mamdani dan Sugeno merupakan dua sistem inferensi paling sering sering digunakan di Matlab, algoritma Mamdani digunakan untuk menentukan output [3]. Metode Mamdani sering juga dikenal dengan nama Metode Max-Min [4][5] [6].…”
Section: Pendahuluanunclassified
“…Logika fuzzy adalah suatu cara yang tepat untuk memetakan suatu ruang input ke dalam suatu ruang output [2]. Sistem Fuzzy Inference (FIS) menggunakan fuzzy set dan aturan "IF-THEN" yang relevan dengan fuzzy set untuk membuat keputusan tentang informasi yang tidak lengkap atau samar, metode Mamdani dan Sugeno merupakan dua sistem inferensi paling sering sering digunakan di Matlab, algoritma Mamdani digunakan untuk menentukan output [3]. Metode Mamdani sering juga dikenal dengan nama Metode Max-Min [4][5] [6].…”
Section: Pendahuluanunclassified
“…In previous works, election results are predicted using fuzzy logic [18]. Autocorrelation methods can be employed to get more accurate results in voting systems.…”
Section: Proposed Workmentioning
confidence: 99%
“…After applying this method it was concluded that this technique plays a pivotal role in election prediction. [37] Harmanjit Singh, et al (2013) designed a simple Graphical user interface (GUI) model based upon fuzzy cognitive maps which is used for predicting the winning chances of a candidate based upon ten different variables. After proper analysis, it was admitted that the proposed model can be used for prediction of the result before the actual result announced, but more parameter needs to be added in order to enhance the better predictability.…”
Section: Wiji Arulampalam Et Al (2008)mentioning
confidence: 99%